Classroom assessment and the National Science Education Standards - National Academy of Sciences - National Research Council, Washington, DC. Center for Education; Atkin, J. Myron; Black, P. J. (Paul Joseph), 1930; Coffey, Janet; National Research Council (U.S.). Committee on Classroom Assessment and the National Science Education Standards (Washington, DC : National Academy Press, 2001)
Since the "National Science Education Standards" were published in 1996, it has become apparent that the standards did not provide sufficient guidance on the key topics needed for implementation. Assessment was identified as a topic requiring more detail and guidance, as well as scientific inquiry, technology in the science curriculum, selection of instructional materials, and development of science programs. This book examines the ongoing assessment that occurs each day in classrooms. Chapters include: (1) "An Introduction to Assessment in the Science Classroom"; (2) "The Case for Strengthening Assessment in the Science Classroom"; (3) "Assessment in the Classroom"; (4) "The Relationship between Formative and Summative Assessment in the Classroom and Beyond"; (5) "Professional Development"; and (6) "Beyond the Classroom--System-Level Supports." (Contains 122 references.) (Author/YDS)
Availability: National Academy Press, 2101 Constitution Avenue NW, Lockbox 285, Washington, DC 20418 (
Contract Number: ESI-9618770.
Contract Number: NCC5-247.
ERIC Note: Produced by the Committee on Classroom Assessment and the National Science Education Standards.
Sponsoring Agency: National Aeronautics and Space Administration, Washington, DC.
Sponsoring Agency: National Science Foundation, Arlington, VA.
Keywords: Elementary Secondary Education; Science -- Ability testing -- United States; Science -- Study and teaching -- Standards -- United States; Science -- Study and teaching -- United States -- Evaluation; Επιστήμη -- Σπουδή και διδασκαλία.; Εκπαίδευση, Δευτεροβάθμια.